Dolly Parton's Christmas of many colors [videorecording (DVD)] : circle of love - Parton, Dolly; Schroder, Rick, 1970-; McRaney, Gerald (Warner Bros., 2016)
The Partons live in the mountains of Tennessee and face a devastating event that challenges their will. When they experience a bewildering Christmas miracle, the Partons are drawn closer together than ever before.